Cloud e-learning in Rural Areas -A Boon in India - Verma, Sunita; Singh, Jagmohan; Joshi , A. S. (Gyan Management Journal, 2015)
This is article covers the need for building a cloud computing infrastructure for rural India which will benefit the regions having lack of resources and awareness. With my motive for keeping up to date on the advances in education, I wondered how cloud computing is impacting the education field. This is an area where a lot of children need help but where money is always in short supply. The problem is further here in rural areas where a majority of the school children go to poorly funded government schools where the requirements of today’s education are nowhere on the priority list. With such sharp contrast, cloud education makes a difference here.